How do women and health care professionals view hormonal long-acting reversible contraception? Results from an international survey. (2nd November 2019) - Faustmann, Thomas; Crocker, John; Moeller, Carsten; Engler, Yvonne; Caetano, Cecilia; Buhling, Kai J.
Abstract: Purpose: Evidence from real-world settings is important to provide an accurate picture of health care delivery. We investigated use of long-acting reversible contraception (LARC) in women aged 15–49 years. Materials and methods: Two surveys, one of women and one of health care professionals (HCPs), were conducted in parallel across seven countries. Participating women completed an online survey to assess contraceptive awareness, current method of contraception, age, and experience with current contraceptive method. HCPs participated in an online survey to provide practice-level information and three anonymous charts of hormonal LARC users. Results: Of 6903 women who completed the survey, 3225 provided information about their current primary contraception method. Overall, 16% used LARC methods, while 52% used oral contraceptives (OCs). Of hormonal intrauterine system users, 72% described their experience as 'very favourable', compared with only 53% of women using OCs. Anonymous patient records ( n  = 1605) were provided by 550 HCPs who completed the online survey. Most women (64%) had used short-acting reversible contraception before switching to LARC. Physicians perceived 56–84% of LARC users to be highly satisfied with their current form of contraception. Conclusions: Although usage of LARC was low, most women using LARC were highly satisfied with their method of contraception.